Reflexiones profesionales sobre la mutación en la elaboración de los contenidos en los medios de comunicación - Barcelli Suarez, Ernesto Rubén (2020)
In this text, the educational profile of the Graduate in Communication is considered, added to his academic training and professional skills, in addition to paying special attention to his field of action: the development of content in journalistic publications, such as the magazines he had at his disposal. position, each oriented towards different target audiences and market segments during the ten years in which she worked in the field of journalism and communication. The most relevant cases of his professional life in this period have also been considered, together with representative cases in his practice as a journalist, explaining in detail the objectives, the description of the cases and the results obtained. In addition, it includes the learnings obtained from their work in the new platforms and digital environments. In this document, the professional has also recorded a list of learning and reflections on his journalistic development; above all, with regard to the changes in the content production processes experienced as a result of the irruption of digital platforms, the consequences of which directly affect the field of communication and the way in which audiences relate to information and communication. cultural industries. In this way, it seeks to contribute to current and future professionals in their development as social communicators and content creators.